Granulometric analysis for the industrial production of copper from chalcopyrite - Romero Baylón, Alfonso (2009)
This research entitled “Particle size analysis for the industrial production of Chalcopyrite”, was performed in the production process as the main product of copper and chalcopyrite as byproduct, the process treats about the reduction in size by milling of ore copper to a size fine enough so that the copper mineral grains are loose. The Project establishes the Granulometric Analysis from the milling of sulfide mineral of Copper of Chalcopyrite to a Laboratory Scale. It has been developed several experimental tests about milling and Granulometric Analysis of sulfide mineral of copper, with the aim of obtaining the milling of a sulfide mineral to a laboratory scale and carry out experimental tests of milling for a range of sizes of mineral in function of the time. In such manner, the reduction of the grains of mineral ask for a milling up to size, which every particles are minor of 100 um of diameter.